Dermatoglyphs in patients with beta-thalassemia major and their thalassemia carrier parents - Dogramaci, Asena C. (Array, 2009)
Abstract: Dermatoglyphs are cutaneous ridges on the fingers, palms, and soles, formed during early intrauterine life. During this period, and only then, genetic and environmental factors can influence their formation. Beta-thalassemia major is a genetic disease. The aim of the present work was to analyze dermatoglyphs traits in subjects with beta-thalassemia major and their thalassemia carrier parents. The sample included 59 patients with beta-thalassemia major (39 males, 20 females). We also analyzed a total of 61 thalassemia carrier parents. There were 38 mothers and 23 fathers in the study. The control group comprised 120 healthy subjects (64 men, 56 women). All ten fingers and right hand palm prints of all participants were taken and statistically analyzed. The results of analyses showed that the frequency of loops on the fifth finger of left hand was significantly higher in female patients than that of carriers and controls (p<0.05). It was also significantly higher in female patients than that male patients (p=0.03). The increase in mean c-d ridge count was noticed in female patients only (p=0.04) compared to carriers and controls. In addition to that there was also differences according to the mean c-d ridge count between female and male patients (p=0.01). Our study showed that dermatoglyphs were helpful for the diagnosis of beta-thalassemia major. However, it does not help to detect thalassemia carriers. This study is the comprehensive dermatoglyphic research on thalassemia, and its dermatoglyphic data will be useful for future research in genetics and medicine